Perspective of Abdullah Munshi as the father of modern Malay literature - Hamdan, Rahimah; Sujud, Arba’ie; Nik Muhamad Affendi, Nik Rafidah (UNIV LAGOS, 2016)
The Western colonization of the Malay world, especially by the British, had a powerful impact on Malay literature. This was consistent with the mission of the colonialists, whereby their presence in the colony would never be forgotten. One effort by the British that will always be remembered to this day is the division of Malay literature into two periods, the traditional and the modern, with the recognition given to Abdullah Munshi as ‘The Father of Modern Malay Literature’. Through two works by Abdullah Munshi, namely Kisah Pelayaran Abdullah and Hikayat Abdullah, Malay literature was introduced to a new literary convention that was ego‐oriented, critical and with themes other than fantasies or fables. Because of this ‘modernity’, Abdullah Munshi was ‘excluded’ by his own audience for challenging the old conventions that had been passed down. It was only almost half a century after his death that budding writers started to copy his writing model. Accordingly, several local and Western scholars emerged to express their views with regard to the recognition given to Abdullah Munshi as the ‘The Father of Modern Malay Literature’. Therefore, the objective of this study was to explain the views of those scholars and to analyse the factors that caused this difference in opinion. This study employed a descriptive method to explain how Abdullah Munshi’s image was created by the West and how the renewal of this lie disturbed the Malay rulers and the community. As a result, ‘The Father of Modern Malay Literature’ successfully fulfilled the goal of the West in Malaya despite the fact that it was offensive to Malay literature itself.